2023
DOI: 10.1371/journal.pone.0282810
|View full text |Cite
|
Sign up to set email alerts
|

A study of autoencoders as a feature extraction technique for spike sorting

Abstract: Spike sorting is the process of grouping spikes of distinct neurons into their respective clusters. Most frequently, this grouping is performed by relying on the similarity of features extracted from spike shapes. In spite of recent developments, current methods have yet to achieve satisfactory performance and many investigators favour sorting manually, even though it is an intensive undertaking that requires prolonged allotments of time. To automate the process, a diverse array of machine learning techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…One of the key reasons for utilizing the autoencoder for feature extraction in the UNSW-NB15 dataset is its capacity to reduce data dimensionality [20]. By learning to represent data succinctly, the autoencoder enables the compression of information while retaining crucial features for intrusion detection.…”
Section: Features Extraction With Autoencodermentioning
confidence: 99%
See 2 more Smart Citations
“…One of the key reasons for utilizing the autoencoder for feature extraction in the UNSW-NB15 dataset is its capacity to reduce data dimensionality [20]. By learning to represent data succinctly, the autoencoder enables the compression of information while retaining crucial features for intrusion detection.…”
Section: Features Extraction With Autoencodermentioning
confidence: 99%
“…The 10 decoding layers perform the inverse operations of the encoding layers to reconstruct the data from the latent code. For each decoding layer 𝑘 ∈ [11,20], the computations are defined by (4).…”
Section: Features Extraction With Autoencodermentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the ubiquity of PCA as a feature extraction method for spike sorting, it lacks robustness to common nuisance variables in extracellular recordings, cannot capture non-linear features of the observed data, and prefers features that explain variance rather than those that discriminate different waveforms. More recently, it has been shown that non-linear autoencoders can have higher performance than PCA despite suffering from similar drawbacks [44].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, variational autoencoders are used to learn a latent data representation that captures the natural clustering of bank customers' data according to creditworthiness [19]. In addition, Typical applications of autoencoders include dimensionality reduction [13] and feature extraction [12,14]. Traditional ways to reduce the dimensionality of large datasets are removing variables with a high correlation and/or a high number of missing values, as well as using PCA (Principal Components Analysis).…”
Section: Introductionmentioning
confidence: 99%